2016
DOI: 10.1002/ajhb.22863
|View full text |Cite
|
Sign up to set email alerts
|

Inverse associations between cardiometabolic risk factors and 25‐hydroxyvitamin D in obese American children and adolescents

Abstract: Vitamin D deficiency is prevalent in obese American children. There was evidence that some cardiometabolic risk factors including lipid levels and oxidized LDL levels were significantly inversely associated with 25(OH)D concentration in our sample. Am. J. Hum. Biol. 28:736-742, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
(65 reference statements)
2
10
0
Order By: Relevance
“…Lastly, in a cross-sectional study of children with obesity (n = 209; age 6-19 years) utilizing age, race/ethnicity, season, and BMI adjusted models, the authors reported that total cholesterol, non-HDL cholesterol, and oxidized LDL were inversely associated with log-transformed 25OHD. 21 In this study, the relationship of lipoprotein ratios TG/HDL and TC/HDL with vitamin D status was not assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, in a cross-sectional study of children with obesity (n = 209; age 6-19 years) utilizing age, race/ethnicity, season, and BMI adjusted models, the authors reported that total cholesterol, non-HDL cholesterol, and oxidized LDL were inversely associated with log-transformed 25OHD. 21 In this study, the relationship of lipoprotein ratios TG/HDL and TC/HDL with vitamin D status was not assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Many recent studies have investigated the association between vitamin D deficiency and cardiovascular risk factors in overweight and obese children [49][50][51][52][53]. Some studies found a higher prevalence of dyslipidemia in vitamin D deficiency obese subjects compared to subjects with vitamin D sufficiency [50][51][52].…”
Section: Vitamin D Deficiency and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Many recent studies have investigated the association between vitamin D deficiency and cardiovascular risk factors in overweight and obese children [49][50][51][52][53]. Some studies found a higher prevalence of dyslipidemia in vitamin D deficiency obese subjects compared to subjects with vitamin D sufficiency [50][51][52]. For example, Censani et al [50] found that overweight and obese children with 25OHD deficiency (<20 ng/mL) had significantly higher non-High Density Lipoprotein (HDL) cholesterol (p < 0.03), total cholesterol (TC; p < 0.01), triglycerides (TG; p < 0.03), Low Density Lipoprotein (LDL) levels (p < 0.03), TG/HDL ratio (p = 0.03), and TC/HDL ratio (p < 0.01) than children with 25OHD ≥20 ng/mL.…”
Section: Vitamin D Deficiency and Cardiovascular Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations